Linking key genes to the stay-green phenotype for climate-smart Triticum aestivum L - Asad Abbas; Jing He; Yuanyuan Wang; Wei Jiang; Afroz Naznin; Rajiv Budhathoki; Jayakumar Bose; Michelle Donovan-Mak; Meixue Zhou; Chengdao Li; Rajeev K. Varshney; Zhong-Hua Chen (BMC Plant Biology)
Abstract Climate-induced heat and drought stress significantly reduce wheat productivity, posing a major challenge, identifying and developing tolerant wheat varieties is a key priority of modern breeding programs. The stay-green phenotype is characterized by sustained photosynthesis and extended grain-filling period under stress conditions, plays a pivotal role in enhancing tolerance. Here, we evaluated 4 commercial Australian wheat cultivars (Coota, Catapult, Beckom, and Sunmaster) in a greenhouse conditions, assessing their physiological, and agronomic traits under heat and combined heat-drought stress. Beckom demonstrated superior heat and combined heat-drought stress tolerance and recovery, maintaining 50% higher photosynthetic and 45% higher transpiration rates in comparison to the sensitive variety, as well as the highest stay-green trait, proline content, and yield. In contrast, Coota exhibited the most severe declines in physiological traits reflecting sensitivity. Expression levels of key genes involved in stomatal regulation, chlorophyll degradation, and heat shock responses in flag leaf tissue showed, significantly higher expression (1.9 and 1.7 folds) of TaGORK (Outward-Rectifying K + channel) gene critical for stomatal regulation is found in Beckom. In contrast, stress-sensitive Coota showed significantly higher expression of (4.5 and 0.68 folds) TaHPX (Haem Peroxidase) and (3.3 and 1.7 folds) TaLOX (Lipoxidase), indicating increased reactive oxygen species (ROS) production and chlorophyll degradation. This study underscores the complexity of physiology processes underlying the stay-green trait and suggests the involvement of multiple pathways including stomatal regulation and chlorophyll degradation. Also, we have identified physiological, biochemical, and genetic traits that may serve as potential phenotypic markers for marker-assisted selection (MAS) aimed at developing tolerant wheat varieties. While these traits show promise, further validation is necessary in future studies, to support sustainable food production in future.